RESEÑA de: Espada, J. P.; Olivares, J.O.; Méndez, F.X. : Terapia psicológica : casos prácticos. Madrid: Pirámide, 2004. - Bausela Herreras, Esperanza (Revista de Psicopatología y Psicología Clínica)
-